ВИКОРИСТАННЯ СУЧАСНОГО ПРОГРАМНОГО ЗАБЕЗПЕЧЕННЯ В СИСТЕМАТИЗАЦІЇ ЛІТЕРАТУРНИХ ДАНИХ ЗА ІНТРАНАЗАЛЬНИМИ ЛІКАРСЬКИМИ ЗАСОБАМИ - Бурлака, Б. С. (Фармацевтичний часопис, 2015)
One of the stages of development of new drugs is a generalization and systematization of existing information flows in the form of scientific abstracts, articles, patents, abstracts, theses, monographs. Often this process for researchers is quite painstaking and consuming, while specialist must possess special skills to find publications, both foreign and domestic origin. It should be noted that the search complicated also a great variety of input data formats which can vary depending on the search engine, database type, nature magazines. Scientific information on medicines intranasal topical and systemic use in a variety of distributed databases and libraries, some fragments of it were published in scientific journals in many languages in the form of abstracts, articles, short communications and patents. Systematics and processing of such information in diverse research causes some complications. Objective. To analyze the art software that can be used to systematize the published data on intranasal drugs. Methods. The material used available software used for organizing research. Served as the Information theses, articles, patents, theses and dissertations on nasal medications. In analyzing the resulting software functionality based on convenience, intuitive and availability. Results and discussion. Initially performed literature search intranasal medicines remotely through internet network in such well-known databases as the US National Library of Medicine (http://www.ncbi.nlm.nih.gov/pubmed/), full-text database ScienceDirect (http : //www.sciencedirect.com/), full-text database Springerlink (http://www.SpringerLink.com), a specialized database "Inventions (Utility models) in Ukraine" (http://sips.gov.ua), specialized DB "Russian patent documents» (http://www1.fips.ru/), scientific digital library eLIBRARY.RU (http://elibrary.ru), national Library of Ukraine Vernadsky (http: // www.nbuv.gov.ua/). As a result of the search were found literary reference with full access to publications and prints without it. As software for working with bibliographic information examined tools such as EndNote ©, Reference Manager ©, ProCite ©, Bible-Master ©, Mendeley ©, Zotero ©. We know that these programs can automate some functions of management science and information retrieval, and can be used by one person or group of people [6]. Having tested the possibility of the above software we stopped at Mendeley © Zotero © and having a similar interface, functionality and freely with each other by exporting it as a universal format RIS and BibTeX. These programs can be used in environments Windows ©, Linux ©, Mac OS ©, are free and easy to use. One advantage of such tools is the ability to synchronize a local base of literature lists and their full texts on selected problem with external servers located in the network internet, which in turn protects against unexpected losses accumulated information and allows you to access your information from anywhere any place. For this Mendeley © Zotero © and can be used free accounts that have a certain amount of disk space in the exhaustion which it is available at an additional cost. In Zotero © along with this is to use your own or free server operating protocol WebDAV (eg "Yandex Disk") that allows you to save free full text publications in the library's own online internet. Through tight integration Mendeley © Zotero © and with a word processor «Microsoft Word» and other applications in the design of scientific publications given the opportunity to conveniently cite evidence from the literature by selecting them from the database, and automatically generate lists of references. Making reference list can change quickly due to the built-in templates or styles (Citation Style Language) which is for many magazines and publishing houses. Currently we conducted the adaptation of literary styles of lists as required GOST 7.1: 2006. Conclusions. As a result, research was conducted search of published data on the development, manufacturing technology and standardization of drugs intranasal administration. It is established that to optimize storage, analysis and processing of data in the literature appropriate to use modern software.